Responsibilities of PT. Bumi Putera Insurance Against Customer Claims Due to Default Actions - Lukum, Silvana; Thalib, Mutia Cherawaty (Universitas Negeri Gorontalo, 2022)
Insurance is the choice for customers in Gorontalo Province. Why is that based on the basic assumption that by insuring the company PT. Bumi Putra Gorontalo Branch will make it easier for customers to send their children to college. However, this hope vanished when many customers of PT. Bumi Putra Gorontalo Branch had problems after maturity and when submitting claims to the insurance company PT. Bumi Putra Gorontalo Branch, the insurer denied insurance payments for tertiary education for children who were insured who were not provided in accordance with the agreement in the PT.Bumi Putra insurance policy. The method used in this research is this type of research is empirical justice research, in other words it is a type of sociological legal research, also called field research. or law in action studies, which are seen from their nature including qualitative research. This legal research is studying the behavior of the people who are influenced by the existence of a rule or the behavior of the people that influences the formation of a rule based on primary and secondary data. Other studies that use inductive logic analysis describe a qualitative approach. Based on the results of the study, the insurance company PT. Bumi Putra, Gorontalo branch, had defaulted on customers in Gorontalo province, but the insurance company, PT. Bumi Putra, the Gorontalo branch, denied that it had not acted in default, but said customers would fulfill their obligations according to what agreed in the insurance policy with the customer.